2010
DOI: 10.1002/adma.200900529
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Bridging Atom on the Performance of a Low‐Bandgap Bulk Heterojunction Solar Cell

Abstract: Bulk heterojunction solar cells have attracted considerable attention over the past several years due to their potential for low-cost photovoltaic technology. The possibility of manufacturing modules via a standard printing/coating method in a roll-to-roll process in combination with the use of low-cost materials will lead to a watt-peak price of less than 1 US$ within the next few years. [1] Despite the low-cost potential, the power conversion efficiency of bulk heterojunction devices is low compared to inorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
357
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 330 publications
(380 citation statements)
references
References 23 publications
23
357
0
Order By: Relevance
“…16(b,c)]. 99,100 The higher crystallinity of the polymer is thought to be responsible for the better charge transport and reduced bimolecular recombination. Thermal annealing was demonstrated to be effective to increase PCE from 3.8 to 5.6%.…”
Section: Polyfluorene-based Polymermentioning
confidence: 99%
“…16(b,c)]. 99,100 The higher crystallinity of the polymer is thought to be responsible for the better charge transport and reduced bimolecular recombination. Thermal annealing was demonstrated to be effective to increase PCE from 3.8 to 5.6%.…”
Section: Polyfluorene-based Polymermentioning
confidence: 99%
“…Several studies have demonstrated that the electronic properties of the polymer 20 backbone can be modified by interaction of the low lying * orbitals of the silicon atom with * orbitals of the conjugated system, primarily resulting in stabilisation of the polymer LUMO in comparison to the carbon bridged analogues. 1 Furthermore studies by Yang 2, 3 , Morana 4 and Scharber 5 et al 25 have directly compared the properties of a silole-containing polymer, poly{ [4,4'- fig 1). They found significant differences in the crystallinity and thin film morphology of the two polymers, which were rationalised on the basis of detailed modelling that the longer carbon-silicon bond in PSBTBT resulted in a 35 reduction of steric hindrance between the solubilising alkyl groups and adjacent thiophene rings.…”
mentioning
confidence: 99%
“…The SiO 2 layer was treated with octadecyltrichlorosilane (OTS) before use, and the Au source drain electrodes were treated with pentafluorobenzene thiol before use to afford a reliable work function. Devices were 5 fabricated by spin coating hot 1,2-dichlorobenzene solutions followed by annealing of the devices at 140°C. The transfer and output characteristics of a typical BG device are shown in fig.…”
mentioning
confidence: 99%
“…Maximum efficiencies were obtained from the blends consisting of the 40% donor loading of Si-PCPDTBT, i. e. a ratio of 0.4:0.6:1 for Si-PCPDTBT:P3HT:PCBM, respectively. An increase in V oc is observed with increasing the Si-PCPDTBT content of the blends, which could be originating from the lower lying HOMO levels of Si-PCPDTBT with respect to P3HT [10]. Such a trend of increasing open circuit voltages has been reported in analogous ternary blends consisting of Si-PCPDTBT [8].…”
Section: Materials and Experimental Methodsmentioning
confidence: 59%